Bedtime routines, development, and caregiver educational attainment in toddlerhood - Lam, Joey Tsz Ying; Williamson, Ariel A.; Salih, Zainab; Heere, Megan; Mindell, Jodi A. (Frontiers in Sleep, 2023)
Background: Implementing a consistent bedtime routine is an empirically supported intervention to improve sleep in toddlers, but little is known about its association with social-emotional outcomes, and among children living in lower socioeconomic status (SES) contexts. Objective: This study examined the longitudinal associations between bedtime routines, social-emotional development, and caregiver educational attainment in toddlers presenting to primary care. Method: Caregivers of 40 toddlers (Mage = 12.85 months, 57.5% female, 62.5% Black/African American) completed questionnaires on sociodemographic factors and child bedtime routine consistency at their 12-month well visit. At the 15- and 24-month well visits, data were collected on child bedtime routine consistency and social-emotional development, including the Brief Infant-Toddler Social and Emotional Assessment (BITSEA) for social-emotional problems and competency and the Ages and Stages Questionnaire (3rd edition; ASQ-3) to assess communication and personal-social skills. Results: Overall, the majority of families engaged in a consistent bedtime routine (5 nights/week) at all time points (63% at 12 months, 75% at 15 months, and 86% at 24 months). Controlling for concurrent bedtime routine consistency, toddlers with a more consistent bedtime routine at 12 months exhibited less dysregulation at age 15 months. Toddlers without a consistent bedtime routine at 15 months exhibited more externalizing and internalizing problems and dysregulation at 24 months. Furthermore, there was a significant interaction between bedtime routine consistency at 15 months and caregiver education for internalizing problems at 24 months, such that toddlers of caregivers with a high school education or less who lacked a consistent bedtime routine showed the most internalizing problems. Conclusions: Clinicians should consider recommending that families with toddlers incorporate a nightly bedtime routine not only to improve overall sleep health, but also to potentially optimize toddlers’ positive social-emotional and behavioral trajectories, especially in families with lower educational attainment.